Self-esteem among emerging adult women experiencing fatherlessness - Tatan Fathmay Lora; Mochamad Widjanarko (Inovasi Kurikulum, 2026)
The phenomenon of fatherlessness remains widespread in Indonesia and can impact children’s psychological development, particularly among young adult women. A father’s physical, emotional, or psychological absence has the potential to influence the development of self-esteem. This study aims to analyze aspects of self-esteem among young adult women who have experienced fatherlessness and its impact on learning. This study employed a qualitative method with a phenomenological approach, focusing on three young adult women who grew up without a father. Data were collected through in-depth interviews and analyzed thematically based on aspects of self-esteem, including power, significance, virtue, and competence. The results indicate that all participants experienced obstacles in the development of their self-esteem, characterized by low self-confidence, difficulty establishing a sense of self, doubts about personal abilities, feelings of worthlessness, and difficulty forming interpersonal relationships. This, of course, impacts their motivation and academic achievement. The absence of a father figure contributed to the emergence of various emotional and psychological problems that affected the informants’ lives into early adulthood, including their learning processes. This study concludes that growing up without a father influences the formation of self-esteem in young adult women in terms of self-power, self-significance, self-virtue, and self-competence.   Abstrak Fenomena fatherless masih banyak terjadi di Indonesia dan dapat berdampak pada perkembangan psikologis anak, khususnya perempuan dewasa awal. Ketidakhadiran ayah secara fisik, emosional, maupun psikologis berpotensi memengaruhi pembentukan self-esteem. Penelitian ini bertujuan untuk menganalisis aspek-aspek self-esteem pada perempuan dewasa awal yang mengalami fatherless serta dampaknya dalam pembelajaran. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis terhadap tiga perempuan dewasa awal yang mengalami fatherless. Data diperoleh melalui wawancara mendalam dan dianalisis secara tematik berdasarkan aspek self-esteem yang meliputi power, significance, virtue, dan competence. Hasil penelitian menunjukkan bahwa seluruh informan mengalami hambatan dalam perkembangan self-esteem, yang ditandai dengan rendahnya rasa percaya diri, kesulitan membangun identitas diri, keraguan terhadap kemampuan pribadi, perasaan kurang berharga, serta kesulitan menjalin hubungan interpersonal. Hal ini tentunya berdampak pada motivasi dan prestasi belajar mereka. Ketidakhadiran figur ayah berkontribusi terhadap munculnya berbagai permasalahan emosional dan psikologis yang memengaruhi kehidupan informan hingga masa dewasa awal, termasuk dalam proses pembelajaran. Penelitian ini menyimpulkan bahwa kondisi fatherless berpengaruh terhadap pembentukan self-esteem perempuan dewasa awal pada aspek kekuatan diri, keberartian diri, kebajikan diri, dan kompetensi diri. Kata Kunci: dewasa awal; fatherless; motivasi pembelajaran; self-esteem